(3Md GdQehR heaGJjM GdcfhRs - (3GdebOSj, GHf ZGfe, YR GdOjf, YHO GdSdGe Hf CMeO Hf ZGfe, (B678 (3g`s
(3ChdgG (B:s
(3bGdYR GdOjf YHO GdSdGe CMeO Hf ZGfe GdebOSjGdMeO ddg GdPj aJM HeaGJjM GdZjhH EbaGd GdbdhHhHYO aEfg deG cGfJ GdeYGfj LhGgQhEfj QCjJ cKjQG ef GdCdaGX bO GQJHc aj EfeGVgG cKjQ ef Cgd GdGYJQGV hCMHHJ Cf CTQM efgG eG GfTQM dg UOQj hSejJgG Md GdQehR heaGJjM GdcfhRs
(3BNQgG (B:s
(3aHge Edjc hSjdJj jG SjOj EdG hUdJ MH dge HMHGdj hCNjHI GdCeGdj Ef CbVjJfj Yf HGHge jG NjHI GdBeGds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 3 / 355s
(3eYLe GdeDdajf(B: 2 / 145s
(3cTa GdXfhf(B: 1 / 686s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs